2,6-Bis(2-Benzimidazolyl)Pyridine (BBP) Is a Potent and Selective Inhibitor of Small Conductance Calcium-Activated Potassium (SK) Channels - Simó-Vicens, Rafel; Bomholtz, Sofia H.; Sørensen, Ulrik S.; Bentzen, Bo H. (Frontiers in Pharmacology, 2018)
A variety of polycyclic pyridines have been proposed as inhibitors of the small conductance calcium-activated potassium (SK) channel. To this group belongs 2,6-bis(2-benzimidazolyl)pyridine (BBP), a commercially and readily available small organic compound which has earlier been described in a broad range of chemical and biological uses. Here, we show how BBP can also be used as a potent and specific SK channel blocker in vitro. The potency of BBP was measured using automatic patch clamp on all three SK channel subtypes, resulting in similar IC50 of 0.4 µM. We also assessed the selectivity of BBP on a panel of calcium-activated and voltage-activated potassium channels using two-electrode voltage clamp, automatic and manual patch clamp. BBP did not have any effect on IK, Kir2.1, Kir3.1+Kir3.4, Kv1.5, Kv4.3/KCHIP2 and Kv7.1/KCNE1 currents and was 4.8-fold and 46-fold more potent on all SK channel subtypes versus BK and hERG channels, respectively. Moreover, we were able to identify H491 as a critical amino acid for the pharmacological effect of BBP on the SK channel. From a medicinal chemistry perspective, BBP could be used as a starting point for the design of new and improved SK inhibitors.